COMPUTER SELF-EFFICACY AND COMPUTER ANXIETY AS PREDICTOR OF RESEARCH ATTITUDE IN HIGHER EDUCATION: AN EMPIRICAL STUDY OF COLLEGES OF EDUCATION IN SOUTH EAST NIGERIA - Ezugwu, Lilian M. (Journal of Advance Research in Social Science and Humanities (ISSN 2208-2387), 2022)
The colleges of education in Nigeria are an essential component of the higher education ecosystem saddled with training future teachers. However, a growing indication suggests a poor research attitude in the colleges of education. Although, the constrictions impeding efficient and globally competitive research development in the higher education system have been emphasized in the literature. However, the construct of computer anxiety and its effect on computer use instigated the current paper. Thus, the study's primary purpose is to examine research attitudes in colleges of education based on computer anxiety. Ninety-six academic staff pooled from the CoE in the Enugu States of Nigeria completed a self-report measure. The linear regression analysis conducted to test the study hypothesis revealed that computer anxiety statistically significantly predicted research attitudes in CoE at F (1,94), 60.031, P<.000. The R2 indicated that the predictor variable explained about 22.1% of the observed variance in research attitudes in CoE. The paper concluded that computer anxiety determines research attitude in CoE.